Two-photon polymerization of alginate hydrogels for applications in cell culture - Henning, Irene (2020)
This work presents two-photon polymerization (2PP) of microstructured 3D hydrogels using alginate for the first time. Alginate is one of the most prevalent biopolymers used for hydrogels due to its biocompatibility, reversible ionic gelation and natural abundance. 2PP enables the fabrication of structures with sub-micron feature size, on the scale of single cells. Combining the high resolution of 2PP with the hydrogel properties of alginate, enables control of the mechanical and geometrical properties of artificial micro-environments. To provide a curing mechanism using 2PP, alginate is functionalised with methacrylate groups using an amidation reaction. The 2PP photoresist is composed of methacrylated alginate dissolved in water and a cyclic benzylidene ketone-based photoinitiator, P2CK, developed for efficient 2PP of biocompatible water-soluble photoresists. To investigate the 2PP characteristics of methacrylated alginate, various photoresist compositions were systematically studied in relation to the alginate concentration, the viscosity and the degree of functionalisation with crosslinking groups of alginate. This revealed that higher degrees of functionalised alginates featured lower polymerization but higher damage-threshold powers resulting in the largest dynamic power ranges. Increasing concentrations of alginate reduced the deformation of all alginate hydrogels. Stable 3D hydrogels could be fabricated using at least two weight percent for alginates functionalised with 30 percent or more methacrylate groups. Optimal printing parameters were identified for alginate photoresists that enable efficient 2PP of hydrogels with high structural integrity. An unprecedented resolution for alginate hydrogels was demonstrated with minimal linewidths down to 175 nm for two weight percent alginate with 30 percent functional groups. The alginate hydrogels were probed for potential cytotoxic effects on bacterial and mammalian cells. A representative for Gram-negative and a Gram-positive bacteria grown on a set of different micro-topographies resulted in distinct differences of bacterial attachment which could be exploited to prevent bacterial growth. The microfabricated alginate hydrogels were further shown to support the growth of human mesenchymal stem cells (hMSCs) with first results indicating that microstructures influence the attachment and morphology of hMSCs cultured for 48 hours. 2PP of alginate allows for precisely engineering artificial cell environments which may enable novel tissue engineering strategies and microbiology investigations. The increased understanding of the variables influencing 2PP of alginate will inform and accelerate the development of other novel water-based photoresists for 2PP.